Implementing energy efficiency measures: do other production resources matter? A broad study in Slovenian manufacturing small and medium-sized enterprises. (10th March 2021) - Trianni, A.; Cagno, E.; Dolšak, J.; Hrovatin, N.
Abstract: Literature has largely investigated barriers to energy efficiency in industrial firms. Recently, research is looking at the non-energy benefits accompanying the adoption of energy efficiency measures that may contribute to overcoming these barriers. In our study we take an innovative perspective by specifically exploring the relationships between energy efficiency measures and other production resources, being assessed by their importance and capability of firms to manage them efficiently. By analysing 10% of Slovenian small and medium-sized manufacturing firms, our exploratory findings show that decision-makers carefully look at the multiple effects (either positive or negative) energy efficiency measures may have on a number of other production resources, particularly on those closer to the production (shop floor). Additionally, companies seem to struggle in efficiently managing the most important production resources, thus suggesting that energy efficiency measures should be looked in close consideration to other resources, which represents a new barrier to energy efficiency not accounted by previous research. Further, we could not detect significant differences between clusters of small versus medium-sized firms and energy intensive versus non-energy intensive ones, differently from previous research that was emphasizing the larger perception of barriers in smaller and less energy intensive firms. Our findings may challenge the discussion over incentive schemes for energy efficiency measures by promoting those with the largest (positive) implications for other production resources. Highlights: Energy efficiency measures have an impact on other production resources. A broad investigation among manufacturing SMEs. Companies consider other production resources when deciding over EEMs. More energy intensive SMEs do not give higher priority to energy.